Análise espacial de indicadores de desenvolvimento socioambiental urbano das regiões norte, noroeste e meia ponte do município de Goiânia (1975 – 2015) - Ramos, Helci Ferreira (2016)
The growth and expansion of the urban environment in cities and to determine the whole dynamics of urban space appropriation, according to the logic of capital which, in most cases, is arbitrary and unequal. Thus, phenomena such as socio-spatial segregation gain strength to the extent that certain populations are forced to live in the outskirts of large cities, thus deprived of access to land, public services and social assistance. This work has as study area the North, Northwest and Mid Bridge regions, both belonging to the Metropolis of Goiânia, being the main cut within these regions, to understand the local dynamics, the census sector. The objective of this study was to evaluate the quality of urban life of the aforementioned regions, using methods to analyze the land issue, calculation of the green area index per capita as well as, of urban socio-environmental segregation patterns. Among the materials and methods used we can highlight the use of orbital data (Landsat 1, 2, 5 e 7) and suborbital aerial photographs (Goiânia prefecture) and IBGE census data (Census 2010), for the information processing the programs were used (Spring 5.3, ArcMap 10.1, ENVI 5.0), all licensed in the Laboratory of Image Processing and Geoprocessing - Lapig / UFG. The main methods used to analyze the data were the dasimetric. Spatial Analysis (Moran Index) and Digital Image Processing - DIP for the definition of the Index of Green Areas (IGA). Regarding the main results of this study we can highlight them in three axes being the first the land issue and urban growth occurred from the 80's, which resulted in the demand for housing, and the emergence of various clandestine settlements and invasions. The research points to 117 lots and lots without land information, 133 allotments with regular status together the supervisory bodies and 144 lots with irregular situation and 144 lots with irregular situation. The second axis of results are the green areas as an indicator of urban quality of life, the study presents a total of 201 public green areas (Squares, APP, APA and Parks) that were mapped. In addition, the Green Areas Index (BTI) was calculated by inhabitants for the three regions, presented a total of 243.52 m² / hab., index that is higher than the one recommended by the United Nations (UN) that defines for Latin America and Caribbean 9 m² / hab. And last line of research results are analyzes of socio-spatial segregation. The study points out that the problems of socio-spatial segregation of social exclusion / inclusion, are present in the three regions. In the analyzes, the Northwest Region is the most problematic, because it presented clusters in most of the variables of social and environmental indicators analyzed. Exclusion / inclusion problems are concentrated in the North-West and North, mainly of the history of implantation of the existing subdivisions and neighborhoods.